Pengaruh Tepung Daun Gamal (Gliricidia sepium) Terfermentasi Dalam Pakan Terhadap Pertumbuhan Benih Ikan Bawal Air Tawar (Colossoma macropomum) - Darmia Sari; Suraiya Nazlia; Dedi Fazriansyah Putra (Journal of Aquaculture Science, 2024)
Gamal leaves have good potential to be used as an alternative feed ingredient for herbivorous and omnivorous fish species. The aim of this research is to determine the effect and optimal dose of adding fermented gamal leaf flour as a feed ingredient on the growth of freshwater pomfret seeds (Colossoma macropomum). The test fish used in this study were freshwater pomfret fish (C. macropomum) with a body length of 6.3–7 cm and weight of 2.6–4.12 g. Experimental fish were maintained at a stocking density of 10 fish/container for 40 days. Feeding is carried out at 07:00 WIB, 12:00 WIB, and 17:00 WIB. The research method used a Completely Randomized Design (CRD) method with six treatments and three replications. Treatment A did not add fermented gamal leaf flour (0%), treatments B, C, D, E, and F added fermented gamal leaf flour 10%, 20%, 30%, 40%, and 50%. The addition of fermented gamal leaf flour in feed had an effect (P<0.05) on absolute growth in length and weight, specific growth rate, feed utilization efficiency and feed conversion ratio, but had no effect (P>0.05) on the viability of pomfret seeds. tasteless (P<0.05). The best growth results were obtained in treatment E (40%), with absolute length and weight growth values of 2.01 cm and 1.81 g, specific growth rate of 4.54%/day, feed conversion ratio of 1.48, and feed utilization efficiency 68.78%.